Mass Transfer Enhancement of Gas Absorption by Adding the Dispersed Organic Phases - 张志刚 许天行 李文秀 纪智玲 许光荣 (Chinese journal of chemical engineering, 2011)
Mass transfer enhancement of gas absorption by adding a dispersed organic phase has been studied in this work. Various dispersed organic phases （heptanol, octanol, isoamyl alcohol, heptane, octane, and isooctane） were tested respectively in the experiment. According to the theoretical model and experimental data, the overall volumetric mass transfer coefficient and enhancement factor were obtained under different dispersed organic phase volume fraction and stirring speed. The experimental results indicate that gas-liquid mass transfer is enhanced at different level by adding a dispersed organic phase. The best performance of enhancement were achieved with the dispersed organic phase volumetric fraction of 5% and under an intermediate stirring speed of 670 r·min^-1. Among the organic phases tested in the experiment, alcohols show better performance, which gave 20% higher enhance-ment of overall volumetric mass transfer coefficient than adding alkanes.